The Relationship Between Learning Motivation and Academic Achievement of Grade VIII Students at UPTD SMPN 16 Kupang in the 2024/2025 Academic Year - Noviana Maria Dos Santos; Matilda Pia Bone; Gracianus E. T. P. Lejap (Edumaspul: Jurnal Pendidikan, 2025)
This research aims to determine the relationship between learning motivation and the learning achievement of class VIII UPTD students at SMPN 16 Kupang for the 2024/2025 academic year. This research is a type of quantitative research. The variables in the research are the independent variable (X) learning motivation and the dependent variable (Y) learning achievement. The sample in this study consisted of 60 class VIII students at SMP Negeri 16 Kupang for the 2024/2025 academic year. The data collection tool used was a questionnaire. Data analysis used the Pearson correlation technique and processed using the SPSS version 24 for Windows application. The results of data analysis show a correlation coefficient of 0.412** and significance of 0.004<0.05. The results of research data analysis show that there is a relationship between learning motivation and student learning achievement at a moderate level, because the correlation coefficient value obtained is 0.412** in the coefficient interval of 0.40-0.599. Furthermore, the level of moderate relationship between learning motivation and student learning achievement can be explained based on the results of the determination test which shows that the contribution of the learning motivation variable is 17% to student learning achievement.